Exploring Student Voices : A Discourse Analysis of EFL Classroom Interaction - Rahma, Putri Triana Shinta; Irmayani, Irmayani (JR-ELT (Journal of Research in English Language Teaching), 2025)
In Indonesia, this study investigates how student voice is both constructed and restrained in EFL classrooms, using discourse analysis of classroom interactions in two senior high schools. The data was collected from four observed lessons, and analysed for patterns in turn-taking, speech function, and code-switching. The findings indicate, classroom talk is primarily dominated by teachers using the IRF pattern that constrains student voice. However there was improvement in student engagement and verbal output when teachers used dialogic strategies such as open-ended questions and scaffolding. Code-switching also emerged as an effective way to increase participation. These findings highlight the need to shift from teacher-centred, monolingual, and display pedagogy to more student-centred, multilingual and discourse aware approaches to teaching that promote teacher-learner participation and voice in EFL classrooms.